Association Between eHealth Literacy in Online Health Communities and Patient Adherence: Cross-sectional Questionnaire Study - Xinyi Lu; Runtong Zhang (JMIR Publications, 2021)
BackgroundeHealth literacy is significantly associated with patients' online information behavior, physician-patient relationship, patient adherence, and health outcomes. As an important product of the internet, online health communities (OHCs) can help redistribute idle medical resources, increase medical resource utilization, and improve patient adherence. However, studies on eHealth literacy in OHCs are limited. Therefore, this study examined patients' eHealth literacy regarding health information-seeking behavior and physician-patient communication in OHCs. ObjectiveThis study aimed to investigate the association between eHealth literacy in OHCs and patient adherence by employing social cognitive theory. MethodsThis was an empirical study, in which a research model consisting of 1 independent variable (patients' eHealth literacy), 3 mediators (physician-patient communication in OHCs, patient health information-seeking behavior in OHCs, and patients' perceived quality of health information in OHCs), 1 dependent variable (patient adherence), and 4 control variables (age, gender, living area, and education level) was established to examine the associations. Multi-item scales were used to measure variables. An anonymous online survey involving 560 participants was conducted through Chinese OHCs in July 2018 to collect data. Partial least squares and structural equation modeling were adopted to analyze data and test hypotheses. ResultsThe survey response rate was 79.6% (446/560). The reliability, convergent validity, and discriminant validity were acceptable. Age, gender, living area, and education level were positively associated with patient adherence, and gender was positively associated with physician-patient communication and patients' perceived quality of internet health information in OHCs. Patients' eHealth literacy was positively associated with patient adherence through the mediations of physician-patient communication, internet health information-seeking behavior, and perceived quality of internet health information in OHCs. ConclusionsResults indicate that physician-patient communication, internet health information-seeking behavior, and the perceived quality of internet health information are significantly associated with improving patient adherence via a guiding of eHealth literacy in OHCs. These findings suggest that physicians can understand and guide their patients' eHealth literacy to improve treatment efficiency; OHCs' operators should this strengthen the management of information quality, develop user-friendly features, and minimize the gap between the actual and perceived information quality.